PREVENTIVE STRATEGIES TO FIGHT COMPLICATIONS DURING PERCUTANEOUS MULTITRACK BALLOON VALVOTOMY REFINING THE TECHNIQUE - Asharf, Tariq; Memon, Muhammad Anis; Rasool, Syed Ishtiaque; Patel, Najma; Panhwar, Ziauddin; Farooq, Fawad; Saghir, Tahir; Qamar, Nadeem; Zaman, Khan Shah-e- (Journal of Ayub Medical College Abbottabad, 2014)
Background: Percutaneous mitral valvuloplasty (PMV) is still the treatment of choice in selected cases of mitral stenosis (MS). Multitrack balloon (MTB) catheter is one of the techniques used for PMV with optimal results. We describe a novel refinement of appropriate balloon sizing and wire placement to reduce mitral regurgitation (MR) and Left ventricular (LV) apical perforation, respectively. Methods: Ninety four consecutive patients with moderate to severe rheumatic mitral stenosis (MS) were selected for PMV with MTB catheter. Balloon sizing was done by effective balloon dilatation area (EBDA), using standard geometric formula. 0.35Ë PMV wire was placed in aortic arch /ascending aorta (AA) to avoid LV apical perforation. Results: Mild MR was present in 28(29.8%). Post-procedure MR was present in 50(53.2%). Out of 50 MR cases 44(88%) had mild and 6(12.0%) had moderate MR. No patient had severe MR. With placement of wire in AA and arch of aorta none of the patients developed complication of LV apical perforation. Conclusion: EDBA as balloon sizing for multitrack system can be used to reduce severity of mitral regurgitation. Placement of PMV guide wire in Aortic arch/AA ascending aorta can eliminate/substantially reduce dreadful complication ofLV perforation. Keywords: Multitrack Balloon Catheter, Balloon Sizing, PMV Guide Wire